Developing Implementation Strategies for the Adoption of the Enhanced Recovery After Surgery (ERAS) Protocols: A Co‐Design Study - Georgia Tobiano; Joan Carlini; Wendy Chaboyer; Rhea Liang; Keith Addy; Linda Sung; Brigid M. Gillespie (Health Expectations)
ABSTRACT Background The clinical effectiveness of Enhanced Recovery After Surgery (ERAS) protocols in reducing length of stay and postoperative complications is well established. Yet, the uptake of these protocols remains variable in many healthcare settings. Methods We used the Generative Co‐Design Framework for Healthcare Innovation to design and deliver strategies to implement ERAS protocols at one Australian tertiary hospital. Co‐design groups included surgeons, anaesthetists, perioperative and surgical nurses, and health consumers with previous surgery experience. Two workshops with co‐designers were held over 4 months. Textual data derived through workshop artefacts and discussions were analysed inductively. Then, subcategories representing implementation strategies were deductively mapped to the level they primarily target, individual, team and organisation. Finally, using a consensus‐building approach, the top two implementation strategies were ranked across each group. Results In total, 36 practitioners across perioperative, ward, surgery and anaesthetics and 4 consumers participated in the co‐design sessions. Through the analysis, 16 implementation strategies were identified, and half of these were aimed at the organisational level. Strategies ranked in the top two commons across all groups of practitioners included reviewing clinical pathways and processes. Consumers believed receiving patient education about ERAS, including its risks and benefits, was essential. Conclusion Our findings underscore the intricate nature of coordinating diverse stakeholders in co‐design processes. Despite the challenges this may present, it provides valuable insights and promotes consensus‐driven solutions, ultimately strengthening the implementation of ERAS initiatives. Patient or Public Contribution Consumers were involved in the co‐design process and were co‐researchers.